Commemorating Martial Law as Treason. Issue 4 (November 2022) - Rossmiller, Ela
How and why have Polish state institutions constructed an official public memory of martial law (1981–1983) despite plural interpretations and growing apathy and amnesia in the broader society? Between 1992 and 2018, parliament passed eight commemorative resolutions endorsing a single interpretation of martial law as treason. This political consensus is surprising given not only the lack of social consensus but also the political polarization that existed between and among post-communist and post-Solidarity parties. Drawing on LaClau and Mouffe's discourse theory as well as Brian Grodsky's theory of transitional justice measures as political goods, this article analyzes the official discourse of martial law as articulated in commemorative resolutions, transcripts of parliamentary deliberations, parliamentary journals, court rulings, and reports of committees, subcommittees, special commissions, and governmental offices. It considers how this discourse has been deployed to legitimate the ruling elite, attack political rivals, and justify controversial initiatives, policies, and reforms. It contributes to the literature on the politics of memory during times of political transformation by examining a case of surprising stability despite factors that would seem to favor change over time.